Integration of Minangkabau Ethnoecology in Biology Education: Analysis of Student Needs - Chairul Amri; Helvita Roza; Sofia Wira (Postgraduate, University of Mataram, 2025)
This study analyzed high school students’ needs regarding the integration of Minangkabau ethnoecology into biology education to support sustainability-oriented learning. Using a mixed-method design, quantitative data were obtained from a validated 20-item Likert-scale questionnaire and qualitative insights were obtained from open-ended questions. The sample involved 666 students from 14 senior high schools in West Sumatra, representing diverse ecological and cultural settings. Statistical analyses—including reliability testing (α = 0.807), normality, homogeneity, and one-way ANOVA—confirmed data consistency and revealed no significant differences among schools (p = 0.085), indicating homogeneous perceptions. Descriptive findings showed high mean scores in learning preferences (M = 4.23), material needs (M = 4.35), and expectations (M = 4.12), reflecting strong demand for contextual and culture-based biology learning. Qualitative responses supported these results, revealing that students linked conservation with traditional practices such as gotong royong, rimbo larangan, and lubuk larangan. These findings highlight the need to design ethnoecology-based biology modules aligned with SDG 4 (Quality Education) and SDG 15 (Life on Land), ensuring culturally grounded and ecologically meaningful science learning.